Under Critical Scrutiny A Normal Task for Swedish Executive Municipal Healthcare Managers - Wramsten Wilmar, Maria; Jacobsson, Christian; Ray, Jeremy; Dellve, Lotta; Låstad, lena (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
Swedish Human Service Organisations (HSOs) operate under high demands of transparency. In this study, executive municipal healthcare managers’ dealings with the Media were mapped. 81% had experiences of dealing with the Media under critical scrutiny. 20% of the respondents were aware of whether their organisation had a media strategy. The respondents received support during media scrutiny mainly from their management team, subordinates, family and friends. The respondents who received support from their management team or the communication department felt that the depiction of their organisation was more correct. The results indicate that a strategy including activities from the management team or the communication department would contribute to managers feeling more satisfied with media depictions of their organisation.